A Unique Case of Recurrent Upper Gastrointestinal Bleeding Caused by Two Metachronous Dieulafoy's Lesions: The Role of EUS Evaluation - Brito, M (2021)
Introduction: Dieulafoy's lesion (DL) is a rare but important cause of acute, severe, life-threatening, and recurrent upper gastrointestinal bleeding (UGIB). It is frequently difficult to diagnose DL with upper GI endoscopy (UGIE), and endoscopic ultrasonography (EUS) may be valuable. There are only 2 reported bleeding cases caused by two synchronous DL but no reported cases of two metachronous DL. Case report: A 28-year-old healthy male presented with acute severe UGIB. UGIE was inconclusive. Systematic EUS mapping identified a gastric DL. After several attempts of EUS-guided hemostasis, DL was marked using a through-the-scope clip and the patient underwent successful transcatheter arterial embolization (TAE). Three years later, a new severe UGIB episode was caused by a second gastric DL in a different location, which was identified and marked by EUS and further successfully treated through TAE. The patient maintained follow-up without evidence of further bleeding. Discussion/conclusion: The authors report a unique case of severe, recurrent UGIB caused by two metachronous gastric DL lesions. The importance of systematic EUS scanning for diagnosis, treatment, and follow-up of DL is emphasized, as well as the potential influence in the outcome of other techniques like angiographic embolization.